Changes in soil organic matter associated with afforestation affect erosion processes: the case of erodible volcanic soils from Patagonia - La Manna, Ludmila; Tarabini, Manuela; Gomez, Federico Antonio; Rostagno, Cesar Mario (Elsevier, 2021)
Large areas of the Patagonian Andean Region with high potential for planting fast-growing exotic conifers, based on the volcanic nature of its soils, are affected by erosion processes. This study aimed to analyse the effects of Pinus ponderosa afforestation on soil organic matter (OM) fractions in non-allophanic volcanic soils and to determine the relationship between organic matter, soil aggregates and erosion processes. The study was conducted along a forested hill slope showing different soil properties according to slope position. OM fractions and aggregate size fractions under different dispersion forces were analysed on 0–5 cm soil samples in rangelands and in 14- and 24-year old plantations on steep and gentle slopes. Simulated rainfall assays were performed to assess soil erodibility; OM and granulometry of sediments were also studied. Results showed that OM contents, mainly OM labile fractions (i.e., particulate OM, and OM associated with macro and large microaggregates), soil aggregation and the formation of very stable microaggregates were enhanced in the afforested soils. However, soil changes varied depending on the initial soil OM contents and on the age of the plantation, with more erratic and smaller changes in most fertile soils. Although potential erosion rates are lower in plantations than in rangeland soils, the high OM enrichment rates found in sediments imply a high OM loss when the soils remain uncovered. Erosion processes in afforestation involve the removal of microaggregates rich in OM and silt fractions, while in the rangelands, coarse and very coarse sand single particles are lost. Afforestation replacing degraded rangelands may be a way to control erosion in these highly erodible volcanic soils, as long as the soil remains covered. Otherwise, the loss of soil enriched in OM from the superficial soil could favour soil carbon depletion.